Caracterização química e proposta de recuperação de elementos nobres de lixo eletrônico - Ferreira, Dennis da Silva (Universidade Federal de São Carlos, 2025)
This thesis addresses the issue of waste electrical and electronic equipment (WEEE), an environmental challenge and an opportunity for urban mining. Globally, 62 million tons were generated in 2022, with only 22.3% recycled, despite containing an estimated value of US$91 billion in metals such as Au, Ag, Cu, and Sn. Given this scenario, the objective of this thesis was to develop and propose a sustainable approach for the chemical characterization and selective recovery of these metals from printed circuit boards (PCBs). The characterization methodology prioritized direct analytical methods to minimize sample preparation and the risk of contamination. Laser-induced breakdown spectroscopy (LIBS) and energy-dispersive X-ray fluorescence (ED-XRF) techniques were used, with complex spectral data being processed by chemometric tools and computational routines developed for this purpose. Principal Component Analysis (PCA) was fundamental for exploratory analysis and for generating hyperspectral images, which allowed the spatial distribution of elements in the samples to be visualized. In addition, strategies for merging LIBS and ED-XRF data with regression models such as MLPCR and ECPR were explored to improve quantification. For metal recovery, a hydrometallurgical route was developed, a more sustainable alternative to traditional pyrometallurgical processes because it operates at temperatures below 100 °C and avoids the formation of hazardous by-products such as dioxins and furans. The method consisted of a sequential leaching process, whose most efficient and environmentally friendly sequence was: i) Cu leaching with HNO3; ii) Sn extraction with HCl; and iii) co-extraction of Ag and Au with an I2/KI solution. The main innovation was the application of LIBS combined with hyperspectral imaging as a real-time process control tool. This approach allowed the efficiency of each leaching step to be monitored quickly, economically, and with spatial resolution. Spatial analysis confirmed the uniformity of extraction, overcoming the limitation of conventional methods that only provide average concentrations. The results, validated by the ICP OES reference technique, confirmed the effectiveness of the process, with recovery rates of 100% for Cu and Ag, 97% for Sn, and 86% for Au. This thesis, therefore, validates a viable technological route for urban mining, promoting the circular economy and offering a sustainable solution for the recovery of electronic waste, with potential application on an industrial scale.
Chemical characterization and proposal for the recovery of noble elements from electronic waste
Keywords: Quimiometria; LIBS; Lixo eletrônico; Hidrometalurgia; ED-XRF; ICP OES; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA